2017
DOI: 10.1186/s12939-017-0627-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical homelessness and candidacy: women transiting between prison and community health care

Abstract: BackgroundWomen in contact with the prison system have high health needs. Short periods in prison and serial incarcerations are common. Examination of their experiences of health care both in prison and in the community may assist in better supporting their wellbeing and, ultimately, decrease their risk of returning to prison.MethodsWe interviewed women in prisons in Sydney, Australia, using pre-release and post-release interviews. We undertook thematic analysis of the combined interviews, considering them as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
6
40
0
Order By: Relevance
“…The perception that some general practitioners are over‐cautious, defensive and perhaps under‐qualified in managing participants' medical problems aligns with another Australian study in women prisoners which found a similar scepticism about general practitioner expertise in the area of addiction (Abbott et al, ). Perceptions (and perhaps the reality) of a general practitioner retreat from medical generalism is of concern because referring on to other medical specialist providers is a relatively ineffective strategy in homeless people, with their high rates of non‐attendance at subsequent appointments.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The perception that some general practitioners are over‐cautious, defensive and perhaps under‐qualified in managing participants' medical problems aligns with another Australian study in women prisoners which found a similar scepticism about general practitioner expertise in the area of addiction (Abbott et al, ). Perceptions (and perhaps the reality) of a general practitioner retreat from medical generalism is of concern because referring on to other medical specialist providers is a relatively ineffective strategy in homeless people, with their high rates of non‐attendance at subsequent appointments.…”
Section: Discussionsupporting
confidence: 52%
“…Admitting to the latter may have presented a more vulnerable, less self‐reliant and stoic image to other homeless people than participants were comfortable with. There is also some evidence that homeless clients constantly need to construct accounts which show themselves to be worthy of services (Marvasti, ), or legitimate ‘candidates’ for care (Abbott, Magin, Davison, & Hu, ). Episodic crises with life‐threatening illness or injury may lend themselves more readily to such accounts than subacute or chronic problems presenting to general practice, and to some extent the apparently dismissive attitudes of hospital‐based practitioners to both general practice and clients may perpetuate this bind.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, barriers to access were perceived by some to be due to racism and discrimination. For women with a background of trauma and abuse, negative interactions with health‐care providers can have profound emotional impacts and difficulty accessing health care in prison can be interpreted as deliberate blocking of care . The pre‐existing relationships and rapport the peer interpreters had with both parties may have decreased some barriers to care.…”
Section: Discussionmentioning
confidence: 99%
“…Using an inductive qualitative approach, we conducted focus groups and individual interviews with CALD women and individual interviews with prison health nurses. This study was undertaken in connection with a larger project into health‐care transitions of women leaving prison …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation